Integrated Water Resources Management on the Southern Slope of the Bamboutos Mountains: Issues Related, Challenges and Prospects - Tchouamani Raoul, Zeugan; Malquaire Rokis, Kue Petou; Tsafack, Hervé (American Scientific Research Journal for Engineering, Technology, and Sciences, 2019)
This research on water resource management was carried out on the southern slope of the Bamboutos Mountains. The main objective of this study was to contribute to a better knowledge and understanding of the problems related to the exploitation of water resources on the southern slope of the Bamboutos Mountains in the hope of finding appropriate management strategies. More specifically, it was a matter of identifying the stakeholders involved in the exploitation of water resources on the southern slope of the Bamboutos Mountains, identifying the problems related to the exploitation of water resources on the said slope, determining the causes and consequences of the problems related to the exploitation of the said resource and finally identifying the strategies, as well as their strengths and weaknesses used by local populations to manage the problems related to the use of water resources. Access to secondary data, and semi-structured surveys allowed the study to be conducted. This study shows that the main actors involved in the exploitation of water resources are farmers, households, industries and finally ranchers. The main problems related to the exploitation of the resource on the said slope have been identified as: conflicts of use (48.60%), water-related diseases (21.30%), distance (18%) and finally the scarcity of the resource (11.90%). These problems have as their causes and consequences respectively: overexploitation of the resource (47.30%), climatic variations (21%), pollution of watercourses (30.40%), struggle between users (54.97%), difficulty of supply (20.50%), and decline in both agricultural and domestic activities (24.53%). In order to solve these problems, local populations have developed strategies ranging from agreement to friendly resolution of conflict problems, construction of health centers for waterborne diseases and construction of alternative and closer supply points to solve distance problems. Despite all these measures, these populations are still struggling to cope with problems that affect their daily well-being.